Resíduos da construção civil na cidade do Recife : percepção de trabalhadores envolvidos - Silva, Luiz Leopoldino Tavares da (2012)
This research aimed to evaluate the perception of some workers involved with the disposal of construction wastes present in the city of Recife. Thus, the investigation of waste from construction in the city of Recife is important considering many are recyclable, which can provide lower costs in the works and the better the quality of life measure that seeks to find ways to reuse of such waste. The methodology adopted to achieve the proposed objectives, consisted of a literature review that addresses the theme, a survey of construction areas licensed in 2011 in Recife, a questionnaire with the construction workers at construction sites; identification and photographing of areas of irregular disposal of waste from construction. Among the local deposition of irregular construction waste can be highlighted: the slopes (which cause overload, condemning the vegetation causing the instability of slopes), watercourses (which undermines the urban drainage and contaminates the water), parks (which allows the proliferation of vectors), and also near hospitals (making the environment more unhealthy). Recycling is now a steady rise in activity and of great importance for the development of the country. It was found that in Recife in the neighborhoods near the center, the buildings have deposits collectors construction waste that are dumped without any separation and are awaiting collection. However in marginal neighborhoods is common view deposition irregular margins county roads, state and federal, highlighting the need for stricter monitoring and comprehensive to the entire municipality and increased investment in information and reuse projects of construction waste in the construction.